Early Modern Privacy Sources and Approaches - Green, Michaël; Nørgaard, Lars Cyril; Birkedal Bruun, Mette (Intersections, 2022)
An examination of instances, experiences, and spaces of early modern privacy. It opens new avenues to understanding the structures and dynamics that shape early modern societies through examination of a wide array of sources, discourses, practices, and spatial programmes.; Readership: Because of its comprehensive disciplinary scope, this volume is of interest to scholars and students of early modern culture in all its facets. Keywords: early modern, intimacy, legal history, religious history, history of art, history of architecture, secrecy, theology, ego-documents, history of science, literary studies, China, Europe, private life, privacy, Jewish history, theory.